CRACKS IN THE FACADE: UNVEILING TRAUMATIC REALITIES IN SHAFAK’S HONOUR (International Journal of Food and Nutritional Sciences, 2022)
The complex and multifaceted nature of honour killing inside the communities has been a major subject of discussion since time immemorial. The diversity of the term with its hidden agenda navigates deep into the lives of common men with rigid rules and customs. Culture favours strict codes regarding honour and upholds integrity by ensuring the smooth functioning of society using the domain of control. They articulate, influence and justify certain modes of behaviours and suggest them as standard patterns of conduct. Honour killing, the vicious practice of exerting dominance over individuals always favours masculine gender by projecting females as weak and powerless. Elif Shafak, a renowned Turkish short story writer and novelist juxtaposes the various ills prevalent in society under the pretext of honour. Shafak in Honour (2011) exposes the realities behind the curtain of Turkish culture and tradition, which centres mainly on the practice of honour killing and its consequences.